British Society for Immunology/United Kingdom Primary Immunodeficiency Network consensus statement on managing non‐infectious complications of common variable immunodeficiency disorders. (7th March 2019) - Bethune, C.; Egner, W.; Garcez, T.; Huissoon, A.; Jolles, S.; Karim, Y.; Jain, R.; Savic, S.; Kelley, K.; Grosse‐Kreul, D.; Grigoriadou, S.
Summary: Common variable immunodeficiency (CVID) represents a heterogeneous group of rare disorders. There is considerable morbidity and mortality as a result of non‐infectious complications, and this presents clinicians with management challenges. Clinical guidelines to support the management of CVID are urgently required. The UK Primary Immunodeficiency Network and the British Society for Immunology funded a joint project to address this. A modified Delphi Survey was conducted for the assessment, diagnosis and treatment of the non‐infectious blood, respiratory, gut and liver complications of CVID. A steering group of 10 consultant immunologists and one nurse specialist developed and reviewed the survey statements and agreed the final recommendations. In total, 22 recommendations and three areas for research were developed.